(untitled) (Research, Society and Development, 2023)
Introduction: Nutritional status is given as “the state resulting from the balance between nutrient supply and energy expenditure”. Changes in nutritional status (malnutrition and obesity) are related to serious health problems. The important influence of monitoring nutritional status during childhood on the growth and development process is highlighted. Objective: to describe the main methods of assessment of nutritional status in children, in order to facilitate the diagnosis of nutritional problems and monitor dietary interventions. Methodology: This is a descriptive research of a brief integrative literature review, which sought to conceptualize nutritional status and nutritional assessment methods in infants. As inclusion criteria, original articles that addressed the research topic and allowed full access to the study content, published from 1999 to 2021, in English, Spanish and Portuguese, were considered. Results: Describes the clinical method, details aspects of anthropometry and laboratory tests used to assess nutritional status. Lists some of the main multiple indices used for both diagnostic and prognostic purposes. In addition, it is able to track, through interviews, possible family repetitions related to hormonal imbalances and metabolic syndromes. Conclusion: Therefore, it is necessary to alert the population to the nutritional risks that may arise during childhood, emphasizing the importance of food re-education and nutrition education activities in schools, which can help in the formation of healthy eating habits, in the maintenance of health and proper body weight control.